The Effect of TIG Welding Parameters and Automatization for Non-Heat Treated Inconel 718 Sheets - NEVCANOĞLU, AKAY; BOZKURT, YAHYA (SPRINGER HEIDELBERG, 2021)
Inconel 718 alloy is widely used in applications that require advanced strength properties especially at high temperature conditions. Combust room walls, exhaust parts, jet tribune blades and gas tribune equipment are the most known using areas. This alloy can be welded with various fusion welding methods, but TIG (Tungsten Inert Gas) welding is preferred since, it provides simply application, mobility and low cost. This study was aimed to clarify that how adjusting the welding parameters and welding automatically can help to achieve promising mechanical properties before heat treatments. The welding experiments were conducted on three different welding current values and attention was paid to provide full penetration for each condition. The results showed that the highest welding current value which did not cause welding defects lead to decrease heat input due to the high transverse speed usage. Moreover, by automatically welding, the heat input was decreased to a minimum level that provided excellent tensile strength and elongation properties. Dendrites turned to cellular from colon. Hazardous zones, such as HAZ and PMZ, narrowed down. The Laves phase ratio and grain size also decreased. Microhardness results confirmed these microstructure observations. The crack observations after tensile tests showed that failures were near HAZ in high-heat input conditions. However, failures were observed in FZ for low-heat input conditions. Additionally, ductile fracture and fracture similar to cleavage mechanisms were observed together due to adjusting the parameters and automatization.
Keywords: Inconel 718; TIG welding; Automatic welding; Welding microstructure; Mechanical properties; Fracture mechanism; MECHANICAL-PROPERTIES; TENSILE PROPERTIES; ACTIVATED FLUX; SUPER ALLOY; MICROSTRUCTURE